2010
DOI: 10.1007/s11130-010-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quinoa Seeds (Chenopodium quinoa) in Diet on some Biochemical Parameters and Essential Elements in Blood of High Fructose-Fed Rats

Abstract: The effect of Chenopodium quinoa seeds on lipid profile, glucose level, protein metabolism and selected essential elements (Na, K, Ca, Mg) level was determined in high—fructose fed male Wistar rats. Fructose decreased significantly LDL [42%, p < 0.01] and activity of alkaline phosphatase [20%, p < 0.05], and increased triglycerides level [86%, p < 0.01]. The analysis of blood of rats fed quinoa indicated, that these seeds effectively reduced serum total cholesterol [26%, p < 0.05], LDL [57%, p < 0.008] and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 28 publications
4
44
0
2
Order By: Relevance
“…The group fed with quinoa showed significantly reduced serum total cholesterol (26%), LDL (57%), TG (11%) and glucose (10%). Fructose significantly decreased HDL (15%) levels in the control group, but when quinoa seeds were added to the diet, the decrease in HDL levels was inhibited [66]. The same research group analyzed fructose administration effects in the same animal groups, and they reported an increase in oxidative stress (high malondialdehyde) in the control group with 31% of its dieting consisting of fructose.…”
Section: In Vivomentioning
confidence: 97%
“…The group fed with quinoa showed significantly reduced serum total cholesterol (26%), LDL (57%), TG (11%) and glucose (10%). Fructose significantly decreased HDL (15%) levels in the control group, but when quinoa seeds were added to the diet, the decrease in HDL levels was inhibited [66]. The same research group analyzed fructose administration effects in the same animal groups, and they reported an increase in oxidative stress (high malondialdehyde) in the control group with 31% of its dieting consisting of fructose.…”
Section: In Vivomentioning
confidence: 97%
“…Quinoa grains contain various phenolics such as quercetin, kaempferol and rutin and their derivatives, vanillic acid, ferulic acid and ferulic acid-4-glucoside (Gomez-Caravaca, Lafelice, Verardo, Marconi, & Caboni, 2014;Gomez-Caravaca, SeguraCarretero, Fernandez-Gutierrez, & Caboni, 2011;Hirose et al, 2010;Tang et al, 2015). In addition, whole grain quinoa in diet was shown to reduce most of the adverse effects exerted by high fructose on lipid profile and glucose levels in rats (Paśko, Zagrodzi, Bartoń , Chlopicka, & Gorinstein, 2010). Furthermore, consumption of quinoa instead of typical products with or without gluten significantly reduced blood sugar, insulin and triglyceride levels in normal as well as celiac patients (Berti, Riso, Monti, & Porrini, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the low internal validity scores were generally Physiological outcomes that were comparatively assessed between animals consuming quinoa and a control diet included weight gain and metabolic outcomes (16 studies), lipid profiles (6 studies) and antioxidant effects (2 studies). Several studies examined a combination of these outcomes, thus explaining the discrepancy between the number of studies included in the review (18) and the number of studies showing physiological outcomes (24).…”
Section: Resultsmentioning
confidence: 99%
“…None of the included studies were able to demonstrate that quinoa had a significant impact on HDL, while only one study showed that a diet containing quinoa was able to significantly lower LDL levels [24]. Interestingly, this study also had the highest dose of quinoa and was performed over the longest time period.…”
Section: Effects On Lipid Profilementioning
confidence: 87%
See 1 more Smart Citation